استبدال جذر الابهر مع الحفاظ على الدسام بطريقة إعادة الزرع طريقة تايرون دافيد - عبد اللطيف, مضر (Latakia University Journal -Medical Sciences Series, 2019)
Background: Aortic valve sparing operations have become more and more accepted as the standard surgical treatment in patients with ascending aortic aneurysm, especially when accompanied by dilatation of the aortic root and aortic regurgitation without deformation of the aortic valve leaflets themselves. The technique described by Tirone David preserves the aortic valve and treats aortic regurgitation at the same time. Recent report of late outcome of this technique have been excellent and very encouraging when used in the right indications. Clinical Cases: We present here three cases of aneurysms of the ascending aorta and aortic root where we used the technique described by Tirone David to resect the aorta and reimplant the aortic valve in a way to restore its normal function and abolish any possible regurgitation. The three patients were operated on by our surgical team in the hospitals of Tishreen University (Lattakia, Syria) with excellent results Conclusion: Aortic replacement with preservation of the aortic valve as described by David is an excellent choice with excellent early and late results and the aortic leaflets should be preserved whenever it is possible مقدمة: طور Tirone David تقنية بديلة لعلاج أمهات دم جذر الأبهر يتم فيها استئصال جدار الأبهر دون الحاجة للتضحية بالدسام الأبهري الذي تبدو وريقاته سليمة و غير مشوهة و من الممكن اصلاح القصور الأبهري في حال وجوده و سميت الطريقة إعادة زرع جذر الأبهر Aortic Root Reimplantation و كانت النتائج مشجعة في حال تم اتباعها في الحالات المرضية المناسبة و الميزة الأساسية هنا هي عدم الحاجة لزرع دسام صنعي بديل و بالتالي تجنب الحاجة لإعطاء المميعات و تجنب المضاعفات المعروفة التي قد تحدث على الطعم الدسامي الصنعي لكن هذه العمليات تتطلب معرفة تامة بالتشريح و دقة كبيرة في التكنيك الجراحي لنجاح الاصلاح الحالات السريرية: نعرض هنا ثلاث حالات جراحية تم فيهما استبدال الابهر الصاعد المتوسع مع استئصال جيوب فالسالفا مع المحافظة على الدسام الأبهري حسب التقنية الموصوفة من قبل Tirone David تم اجراؤها في مشافي كلية الطب بجامعة تشرين و كانت نتيجة العمل الجراحي ممتازة في كل الحالات المناقشة: تعد الجراحة المحافظة على الدسام الأبهري عند استئصال أمهات دم الأبهر الصاعد جراحة متقدمة يجب اتباعها في الاستطبابات المناسبة و هي تتفوق بنتائجها على طريقة Bentall التي تتم فيها التضحية بالدسام الأبهري الطبيعي.